Usability Evaluation for Mobile-Based Nutritional Food Recommender System - Ratih Kartika Dewi; Tri Afirianto; Eva Putri Arfiani; Nabila Fairuz Zahra (Faculty of Computer Science (FILKOM) Brawijaya University, 2023)
COVID-19 was designated as a global pandemic by WHO and Government Regulation of the Republic of Indonesia Number 21 of 2020 concerning Large-Scale Social Restrictions for the handling of Corona Virus Disease 2019 (COVID-19). Eating healthy foods with balanced nutrition can increase the body's immunity during a COVID-19 pandemic. Since many foods that sold freely are not guaranteed in nutritional ingredients, cooking becomes a better alternative. system is a mobile application that provides a recommendation of healthy food recipe by using the Simple Additive Weighting (SAW) algorithm, which has been studied in the previous research of recipe recommendation and gives significant result. Previous research has not examined the appropriate variables and the data are still general food. We conducted a user study to measure the usability of the proposed system. The result of usability testing shows that there is a significant increase in SUS score from 63.5 to 87.